Straits settlements laws [1835-1937] (Petaling Jaya : ,Arkib Negara)
Mengandungia Vol. 5 Edition of 1936 Chapter 186-265. 1937 Suppl. to the Laws of the S. Settlements Part 1 & 2. 1938 Suppl. to the laws of the S. Settlements Part 1 & 2 termasuk Chapter 187 Hospitals Board [6th May 1910]; Cap 189 Destruction of Mosquitoes [8th May 1920]; Cap 192 Tan Tock Seng's Hospital [27th Aug 1880]; Cap 195 Poisons [20th Apr 1905]; Cap 1901 Auctioneers, Licences [1st Jul. 1906]; Cap 199 Measures [1st Jul. 1886]; Cap 213 Traffic Regulation [29th Sept. 1933]; Cap 219 Currency [1st Oct. 1923]; Cap 227 Estate Duty [1st Jul. 1929]; Cap 243 Nederland Sche Handel Muatschappij [22 Jan 1892].